Politeness in language in the undak usuk basa as a local wisdom of the Sundanese people - Asteka, Pipik; Nisya, Risma Khairun; Rahmawati, Ima Siti (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The accelerated progression of globalization and modernization has precipitated a decline in the significance accorded to local wisdom, a hallmark of their ancestral legacy. This phenomenon is particularly evident among high school students, who, as the younger generation, are increasingly drawn to foreign cultures, thereby exhibiting a diminution of interest in their own regional traditions and values. The erosion of local wisdom values among high school students is of particular concern, as these values represent a crucial component of the nation's cultural heritage, the preservation of which is of paramount importance. This article analyzes language politeness in Undak Usuk Basa as Local Wisdom of the Sundanese Community, with the research object being high school students who belong to the Sundanese language community in the Majalengka and Kuningan districts.This research uses a qualitative descriptive research method, and the results show that language proficiency in the usuk basa acts among high school students has been degraded. This decline is evidenced by a noticeable shift in the characteristics of Sundanese individuals, who are traditionally known for their amiable, compassionate, amicable, and courteous dispositions. This transformation is particularly concerning, as it occurs among the next generation, representing the future of local wisdom and Indonesian culture.The findings of this study reveal that high school students exhibit a decline in politeness, as evidenced by their less than courteous language use. This suggests that the use of basa steps in language politeness may serve as a reflection of a person's refinement, characterized by the qualities and characteristics of Sundanese society.